Descriptive Study: Implementation Of Character Education In The Dormitory Of The Indonesian School Of Davao, Philippines - Riski, Yunia Tiara; Huda, Muhammad Nur; Coralde, Marylien Joy Cabulusan; Andajani, Sri Joeda (Universitas Pendidikan Indonesia, 2023)
This study aims to determine the types of character education that are applied or implemented to students who live in the Davao Indonesia School (SID) dormitory. The objectives to be achieved include this research is expected to describe the application of character education in the form of religious attitudes, discipline, national spirit, care for the environment, and responsibility in the SID dormitory and can describe the achievements of character education in the dormitory and its obstacles. This research was carried out for three months starting with asking permission, data collection, analysis, reporting. Data was collected by means of structured interview sheets and documentation studies. The results showed that character education in the SID dormitory had been implemented. The implementation of religious attitudes is carried out through routine worship activities, reading scriptures, religious activities, and appeals for good dress. Discipline is carried out by applying the given rules and dividing individual and group tasks. The attitude of the national spirit is reflected in the obligation to use the Indonesian language, play Indonesian songs, and watch Indonesian films together. The attitude of caring for the environment is instilled through mutual cooperation activities, cleaning pickets, joint activities in supporting environmental cleanliness and reminding each other about cleanliness. The attitude of responsibility is implemented from the willingness to be led, regulated, and directed, to take every advice seriously and to maintain and maintain the objects owned and to carry out the results of the agreements that have been made. Overall, the results of character education in the SID dormitory have a significant impact on the character of students who previously lived and grew up in their hometowns who are not familiar with Indonesian culture at all today. The obstacles to planting character education in SID dormitories are family background and the influence of strong home environment conditions that do not support Indonesian character education and the different characteristics of students.